Breathlessness and restrictive lung disease: an important diabetes-related feature in patients with type 2 diabetes - Kopf, Stefan; Gröner, Jan; Kender, Zoltán; Fleming, Thomas; Brune, Maik; Riedinger, Christin; Volk, Nadine; Herpel, Esther; Wielpütz, Mark Oliver; Kauczor, Hans-Ulrich; Katus, Hugo; Kreuter, Michael; et al. (Respiration, 2018)
Background: Diabetes mellitus is a significant comorbidity of interstitial lung disease (ILD). Objectives: The aim of this study was to investigate the incidence of restrictive lung disease (RLD) and ILD in patients with prediabetes and type 2 diabetes (T2D). Methods: Forty-eight nondiabetics, 68 patients with prediabetes, 29 newly diagnosed T2D, and 110 patients with long-term T2D were examined for metabolic control, diabetes-related complications, breathlessness, and lung function. Five participants with T2D, breathlessness, and RLD underwent multidetector computed tomography (MDCT) and a Six-Minute Walk Test (6MWT). Lung tissue from 4 patients without diabetes and from 3 patients with T2D was histologically examined for presence of pulmonary fibrosis. Results: Breathlessness in combination with RLD was significantly increased in patients with prediabetes and T2D (p < 0.01). RLD was found in 9% of patients with prediabetes, in 20% of patients with newly diagnosed T2D, and in 27% of patients with long-term T2D. Thus, patients with long-term T2D had an increased risk of RLD (OR 5.82 [95% CI 1.71-20.5], p < 0.01). RLD was significantly associated with glucose metabolism and albuminuria (p < 0.01); furthermore, presence of nephropathy increased the risk of RLD (OR 8.57 [95% CI 3.4-21.9], p < 0.01) compared to nondiabetics. MDCT revealed ILD in 4 patients, the 6MWT correlated with the extent of ILD, and histological analysis showed fibrosing ILD in patients with T2D. Conclusions: This study demonstrates increased breathlessness and a high prevalence of RLD in patients with T2D, indicating an association between diabetes and fibrosing ILD.
Gesehen am 17.07.2018